Recruitment and job applications of older jobseekers from the establishments' perspective - Lutz Bellmann; Martin Brussig (Institute for the Study of Labor (IZA), 2007)
In the demographic change, a prolongation of individual employment and thus of beginning a new employment in later stages of the work life is of growing importance. On the base of microeconomic data (establishment panel of the IAB), this paper analyses firms' characteristics correlating with their recruitment behaviour towards the elderly (age 50 and more). Special consideration is given to the labour supply, which is here observed as the existence of an application from job seekers of age 50 and more, and which is a condition for recruiting of older employees. The results show that about 75% of the firms did not have an application of older job seekers. Of the remaining firms, which reported to have applications from older job seekers, about half of the firms recruited older job seekers, and the other half did not so. However, there are remarkable differences between firms which received applications from older job seekers and firms which are willing to recruit older job candidates. Possible explanations point to the search behaviour of job seekers as well as to the signalling of firms on the labour market towards the elderly.
urn:nbn:de:101:1-20080402533
Keywords: 330; Ältere Arbeitskräfte; Arbeitsuche; Arbeitsnachfrage; Offene Stellen; Unternehmen; Deutschland